2004
DOI: 10.1136/jmg.2003.016048
|View full text |Cite
|
Sign up to set email alerts
|

Variable penetrance of a familial progressive necrotising encephalopathy due to a novel tRNAIle homoplasmic mutation in the mitochondrial genome

Abstract: Introduction: We present a family comprising a clinically normal mother and two daughters, each with severe encephalopathy with onset in late childhood. A third daughter had died previously of an earlier onset but neuropathologically similar disease. Methods: Sequence analysis of the entire mtDNA was carried out in muscle, fibroblasts, and lymphocytes of the affected daughters and unaffected mother. Biochemical analysis of individual respiratory chain enzymes was performed on the same tissues, and on several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…However, several recent studies have revealed that homoplasmy, at least in somatic cells, might be a more frequent condition than what originally suggested (Lightowlers et al 1997). This is particularly striking for tRNA mutations that have been reported to be homoplasmic in both affected and nonaffected members of the same family (McFarland et al 2002;Limongelli et al 2004). In this framework, an important feature of the yeast model is that it allows the effect of mutations in homoplasmic conditions to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several recent studies have revealed that homoplasmy, at least in somatic cells, might be a more frequent condition than what originally suggested (Lightowlers et al 1997). This is particularly striking for tRNA mutations that have been reported to be homoplasmic in both affected and nonaffected members of the same family (McFarland et al 2002;Limongelli et al 2004). In this framework, an important feature of the yeast model is that it allows the effect of mutations in homoplasmic conditions to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, skeletal muscle morphology was normal, with a reduction of complexes I and IV. This substitution has been reported to have an extremely variable penetrance in the family where it was detected (Limongelli et al 2004). The three children bearing the m.4290T>C mutation had severe and fatal encephalopathy, while no data are available (e.g., about the levels of suppressor molecules) to explain the asymptomatic condition of the mother.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, milder mutations and heterogeneity can permit survival. 36 Moreover, introduction of normal mitochondrial DNA to mitochondria with mutated DNA by dynamic networking allows an efficient mechanism of mitochondria survival. 37 In addition, random distribution of mitochondria among daughter cells during cell division causes delivery of different proportions of mitochondria containing normal and mutant mitochondrial DNA to each daughter cell which further allows mitochondrial disease free survival of cells and organs.…”
Section: Mitochondrial Genomementioning
confidence: 99%
“…It has been found that patients with higher mutant load have an early onset in childhood because of maternally inherited mitochondrial DNA defects. 36 This reflects the importance of the levels of heteroplasmy influencing the penetration of mitochondrial disorders.…”
Section: Mitochondrial Dysfunctional Diseasesmentioning
confidence: 99%